2023
DOI: 10.3390/land12112079
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Monitoring of Winter Wheat Health in Mining Subsidence Areas by Combined Active and Passive Remote Sensing Technology

Haobin Zhang,
Chao Ma,
Wenbing Guo
et al.

Abstract: The contradiction between efficient coal mining and arable land capacity enhancement in the coal–grain production overlapping area has constrained grain output and threatened food security. In this study, DInSAR was used to extract the mining subsidence areas (SAs). Multiple red-edged vegetation indices were introduced to explore the growth differences between winter wheat in the SAs and Check Areas (CKs). A crop health index (SACHI) was proposed to comprehensively evaluate the health of winter wheat in SAs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The stress of rock mass is redistributed, and this contributes to rock mass fracture and movement. The fracture and movement of rock mass eventually form the ground surface deformation, soil subsidence, cracks, and fractures, and then the condition for crop habitats on the surface has been changed [50]. Previous studies reported that terrain changes caused by mining influence the physical and chemical properties of soil [11,25,51,52], and the phenotype and biomass of above-ground vegetation [12,53].…”
Section: Modeling Of Winter Wheat Agb Estimation In Coal Mining Areamentioning
confidence: 99%
“…The stress of rock mass is redistributed, and this contributes to rock mass fracture and movement. The fracture and movement of rock mass eventually form the ground surface deformation, soil subsidence, cracks, and fractures, and then the condition for crop habitats on the surface has been changed [50]. Previous studies reported that terrain changes caused by mining influence the physical and chemical properties of soil [11,25,51,52], and the phenotype and biomass of above-ground vegetation [12,53].…”
Section: Modeling Of Winter Wheat Agb Estimation In Coal Mining Areamentioning
confidence: 99%